Yuca boletin informativo : Indices de autores y materias 1977-1989 - Menendez F., L. (International Center for Tropical Agriculture, 1991)
Comprehensive author and subject indexes of the Cassava Newsletter, a periodic publication that disseminates the main research results of the cassava researchers` network, are presented for the period 1977-89. (CIAT)